Perspectives of RNAi studies in plant pathogenic fungi - Quốc, Nguyễn Bảo; Châu, Nguyễn Ngọc Bảo (Vietnam Journal of Biotechnology, 2016)
RNA silencing, the phenomenon known as RNA interference (RNAi), co-suppression or post-transcriptional gene silencing (PTGS) and quelling, has become more popular in studies of its intrinsic roles and applications in many organisms or of gene functions in a whole genomic scale. Since the discovery of RNA silencing more two decades ago, this powerful technology has demonstrated its applicability in developing RNAi-based drugs for various diseases in human. RNA silencing is also of interest in basic and applied studies in agriculture, especially in plant protection to create crop varieties that are resistant to biotic and abiotic stresses. This review provides an overview of RNA silencing studies in filamentous fungi, the molecular mechanisms of RNA silencing in fungi, and also describes potential applications in plant protection potentially important for the agricultural industry and for global food security.